Opportunities and Challenges of Business Digitalization: A Case Study of Interest Bucket MSMEs - Andi Indriani Ibrahim; Muh. Riswandi Palawa; Ahmad Kurniawan; Salda Miranti Supriadi; Rezaldy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to examine how micro-business actors utilize digitalization as a strategy to navigate the dynamics of the modern market, as well as to identify the opportunities and challenges they encounter. A descriptive qualitative approach was employed through a case study of Bucket Bunga, a creative florist business that has been operating for seven years and is managed by a young entrepreneur in City X. Data were collected through in-depth interviews with the business owner. The results show that digitalization has had a positive impact on market reach, service efficiency, and increased customer interest through social media platforms such as Instagram and WhatsApp. However, several challenges persist, including limited understanding of social media algorithms, fluctuating content visibility, and the rising competition in the online business landscape. The main strategy adopted by the business owner involves improving product quality and customer service, although no external support has been received from communities or educational institutions. This study highlights the importance of digital literacy and institutional support to help micro-businesses adapt effectively to the digital economy ecosystem.